2019
DOI: 10.1097/meg.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal recall questionnaires compare poorly with prospective patient diaries for gastrointestinal symptoms: data from population and primary health centre samples

Abstract: Background Clinical understanding of gastrointestinal symptoms is commonly based on patient reports of symptom experience. For diagnosis and treatment choices to be appropriate, symptom reports need to be accurate. We examined the agreement between questionnaire recall and prospective diary enumeration of symptoms relevant to the irritable bowel syndrome. Patients and methods Data are reported from a randomly selected general population sample (n=238) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Twelve studies approximated the Rome III criteria using another questionnaire, with a pooled prevalence of 14.0% (95% CI 11.2% to 17.0%). 20,28,30,32,36,50,62,[68][69][70][71]77 Five of the six studies reported prevalence of IBS according to the Rome IV criteria using the validated questionnaire, with a pooled prevalence of 3.6% (95% CI 3.0% to 4.3%). 55,72,76,78,79 The sixth study approximated Rome IV criteria using another questionnaire, 73 with a prevalence of 10.4% (95% CI 8.2% to 12.1%).…”
Section: Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies approximated the Rome III criteria using another questionnaire, with a pooled prevalence of 14.0% (95% CI 11.2% to 17.0%). 20,28,30,32,36,50,62,[68][69][70][71]77 Five of the six studies reported prevalence of IBS according to the Rome IV criteria using the validated questionnaire, with a pooled prevalence of 3.6% (95% CI 3.0% to 4.3%). 55,72,76,78,79 The sixth study approximated Rome IV criteria using another questionnaire, 73 with a prevalence of 10.4% (95% CI 8.2% to 12.1%).…”
Section: Administrationmentioning
confidence: 99%
“…When studies were pooled according to the method of administration of the questionnaire, again there were significant differences in prevalence between individual studies. When the Rome III questionnaire was administered at an interview in 29 studies, 20,22,23,31,[33][34][35]37,[39][40][41][42][45][46][47][48][49][51][52][53]60,61,[65][66][67]69,70,75,79 the prevalence of IBS ranged from 0.4% in India and Ghana, 79 to 20.9% in Singapore, 61 with a pooled prevalence of 5.9% (95% CI 4.6% to 7.4%). When the same questionnaire was self-completed in 22 studies 24,28-30,32,36,38,43,44,50,54,56,58,59,62-64,68,71,77-79 the prevalence ranged from 2.0% in the USA, 58 to 29.2% in Croatia, 24 with a pooled prevalence of 12.0% (95% CI 9.6% to 14.6%).…”
Section: Administrationmentioning
confidence: 99%
“…One study observed that health care providers frequently misinterpret reported symptoms, leading to differences in how the patient and the physician perceive a patient’s current state [68]. As a further challenge, the concordance between a patient’s memory of experience and actual experience of gastrointestinal (GI) symptoms has been observed to be generally poor [69]. The insufficient identification and management of IBD flares is one reason that many patients have poor outcomes [49].…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, data should be collected prospectively to reduce recall error. However, if collected retrospectively to reduce participant burden in cohort studies or for obtaining point-prevalence data from cross-sectional surveys, the length of the recall time-period should be limited preferably to 1 week (5). When calculating AGE incidence, both the AGE episode itself and the minimum length of time separating what would be considered two consecutive episodes (the refractory period) need to be defined (6).…”
Section: Introductionmentioning
confidence: 99%